Synergistic effects of S-alkenylmercaptocysteine (CySSR) species derived from Allium tissue and selenium on inducing apoptosis in ER− breast cancer cells. (February 2020) - Zhang, Wei; Tocmo, Restituto; Parkin, Kirk L.
Graphical abstract: Highlights: CySSR + Se show synergistic anticancer effects. CySSR + Se upregulated GSK3 and activated JNK pathway to induce apoptosis. CySSR reductive metabolites activated Se as H2 Se to contribute on apoptosis induction. CySSPe is similarly potent as the well-studied CySSA in signaling apoptosis. Abstract: S -Allylmercaptocysteine (CySSA) from garlic and its onion analog S -1-propenylmercaptocysteine (CySSPe) show potential anti-cancer abilities. In this study, apoptosis induction by these two S -alk(en)lymercaptocysteine (CySSR) analogs in combination with Na2 SeO3 (Se) was investigated in MDA-MD-231 breast cancer cells. CySSA and CySSPe alone did not affect cell viability, whereas CySSPe + Se and CySSA + Se showed dose-dependent reduction in cell viability. Synergistic effect was confirmed by isobologram analysis. Annexin-V staining and flow cytometric analysis revealed induction of apoptosis. Mechanistically, CySSR + Se upregulated GSK-3α/β and activated p53 to trigger apoptosis. Both CySSR + Se activated JNK pathway at an early stage, but only CySSPe + Se exhibited sustained JNK activation. Inhibition of the cystine/glutamate (xC -) antiporter by sulfasalazine attenuated the antiproliferative effects of CySSR + Se suggesting the involvement of xC - in CySSR + Se − induced apoptosis. This study indicates that the onion analogue CySSPe was similarly as effective as the major studied garlic analogue CySSA in apoptosis induction in ER − breast cancer cells.